Background ducking to produce esthetically pleasing audio for TV with clear speech - Torcoli, Matteo; Freke-Morin, Alex; Paulus, Jouni; Simon, Christian; Shirley, Ben (AES 146th International Convention, 2019)
In audio production, background ducking facilitates speech intelligibility, while keeping the background track enjoyable. Technical details for recommendable ducking practices are not currently documented in literature. Hence, we first analyze common practices found in TV documentaries. Second, a subjective test investigates the preferences of 22 normal-hearing listeners on the Loudness Difference (LD) between commentary and background during ducking. Highly personal preferences are observed, highlighting the importance of object-based personalization. Statistically significant difference is found between non-expert and expert listeners. On average, non-experts prefer LDs that are 4 LU higher than the ones preferred by experts. Based on the test results, we recommend at least 10 LU difference between commentary and music and at least 15 LU between commentary and ambience.
CRIS-Team Scopus Importer:2019-06-21